Climate-adaptive performance index for green roof substrates: year-round assessment in Auckland - Aung Naing Soe; Sihui Dong; Asaad Y. Shamseldin; Kilisimasi Latu; Conrad Zorn; Robyn Simcock; Rachel Devine; Zoe Avery (Hydrological Sciences Journal, 2026)

Optimizing green roof substrates for coastal resilience: Thermal performance and energy implications under extreme weather in Auckland - Sihui Dong; Aung Naing Soe; Asaad Y. Shamseldin; Conrad Zorn; Kilisimasi Latu; Robyn Simcock; Zoë Avery; Minghao Chen; Rachel Devine (Building and Environment, 2026)

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Inequity in nature’s contributions to people in Ōtautahi/ Christchurch: A low-density post-earthquake city - Daniel Richards; Maksym Polyakov; Angela J. Brandt; Jo Cavanagh; Gradon Diprose; Grace Milner; John V. Ramana; Robyn Simcock (Urban Forestry & Urban Greening, 2023)